'We didn't want to leave our island': stories of involuntary resettlement from Gaadhoo Island, Maldives. Issue 2 (4th March 2022) - Azfa, Aishath; Jackson, Guy; Westoby, Ross; McNamara, Karen E.; McMichael, Celia; Farbotko, Carol
ABSTRACT: With development displacing more people and planned relocation being espoused as an adaptation strategy in response to climate change, research that explores the experiences of those who have been resettled is needed. The Maldives has a history of resettlement based on an ongoing policy of consolidation of dispersed populations to ensure access to services. The paper explores the history, politics, and perceptions and experiences of Gaadhoo Islanders in the Maldives during their involuntary resettlement to Fonadhoo Island in January 2016. Through in-depth interviews and ethnographic fieldwork among the resettled, a range of subjective experiences is identified. Although only a small proportion of participants wanted to leave and the process was undemocratic and politically motivated, both positive and negative outcomes were identified. In line with existing research, greater access to services and employment were positive outcomes of the resettlement. However, the process led to non-tangible loss of identity, culture and community cohesion. It is suggested that transparency, consistency and open communication should be central to the process throughout, from pre-decision to the resettlement process itself, and during the compensation and post-resettlement stages. The lessons drawn from this case study may help mitigate potential negative impacts from resettlements which will likely continue and increase into the future.